2003
DOI: 10.1007/s00402-002-0461-0
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcosis granulosus/cysticus of the tibia

Abstract: Hydatid disease is caused by the parasitic tapeworm Echinococcus. There are three species: E. granulosus, E. alveolaris and E. voegeli. Only E. alveolaris and E. granulosus are important for human infections. These two species are totally divergent in their manner of infestation. Hydatid disease is a rare parasitic disease that primary involves the liver and the lung. Skeletal disease is rare, accounting for less than 2% of all hydatid lesions, and often presents as a clinical and radiologic diagnostic problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
1
21
0
5
Order By: Relevance
“…Su distribución más frecuente es a nivel vertebral y en ella la localización torácica con compromiso primario del cuerpo vertebral pudiendo presentar extensión intradural, intramedular y a tejidos blandos paravertebrales; siendo huesos largos (fémur y tibia) y pelvis otras localizaciones frecuentes 11,[12][13][14]20 . De nuestros casos, tres son de localización vertebral y todos ellos de ubicación torácica observándose extensión intraraquidea en todos ellos y compromiso de tejidos blandos en un caso.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Su distribución más frecuente es a nivel vertebral y en ella la localización torácica con compromiso primario del cuerpo vertebral pudiendo presentar extensión intradural, intramedular y a tejidos blandos paravertebrales; siendo huesos largos (fémur y tibia) y pelvis otras localizaciones frecuentes 11,[12][13][14]20 . De nuestros casos, tres son de localización vertebral y todos ellos de ubicación torácica observándose extensión intraraquidea en todos ellos y compromiso de tejidos blandos en un caso.…”
Section: Discussionunclassified
“…Por esta razón su diagnóstico es generalmente difícil y a menudo se hace cuando las lesiones son extensas, diseminadas o por complicaciones derivadas de ella y un porcentaje no menor solo se diagnóstica después de la cirugía 10,[11][12][13][14][15][16][17]21 . Las posibles complicaciones derivadas de la hidatidosis ósea consideran fractura patológica en huesos largos, déficit neurológico por compresión medular en hidatidosis vertebral, extensión a tejidos blandos con fistulización y posible sobreinfección Tenue captación del contraste en la periferia (D).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It has been been suggested that xray and even CT scan of hydatid disease are similar to those of metastases, giant cell tumors, tuberculosis, and bone cysts. Only MRI may aid in the diagnosis of hydatid cyst [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Ranije je postojala sumnja da se zaista radilo o intramedularnoj ehinokokozi, što je naprednijom neuroradiološkom dijagnostikom potvrđeno u malom broju slučajeva [1][2][3][4][5][6][7] .…”
Section: Uvodunclassified